Mercadona : would the benefits of further internationalizing outweigh its risks? - Pereda, Francisco (2023)
This case study analyses the dilemma that Mercadona, the leading retailer in Spain, faces regarding its internationalization strategy. The case starts by going through the company’s history, reviewing its key turning points and evaluating the factors that helped Mercadona achieve the privileged position in the market it now enjoys. Mercadona possesses several attributes that would encourage its management to be brave and optimistic during its strategic decision-making process. Its business model is becoming increasingly popular globally as big supermarkets and hypermarkets gain market share whilst traditional grocery stores seem a thing of the past. The dissertation includes a literature review on topics concerning the internationalization for global retailers and a teaching note with recommendations were made as to what Mercadona’s next steps should be. Although focusing on the Iberian Peninsula, taking into account the challenge Portugal represents, could by no means be considered as a severe misplay, further internationalising into a culturally similar market would be the most beneficial strategic plan.